Inovação social no semiárido: o caso do Projeto Mandalla no Ceará - Costa, Josimar Souza (2013)
The purpose of this work is to analyze the results of the Project Mandalla by the State Government of Ceará from the perspective of social innovation (SI) in the context of semi-arid Northeast Brazil. We used the analytical framework Neumeier (2012) and Butknievice (2010) of the process of social innovation that addresses the stages of diffusion of these new ways of acting and the conditioning factors of a successful implementation, respectively. Currently, the concept of social innovation is often employed in the academic world, but it is still pervasive. In the academic literature there are numerous applications of the term. A systematic review of the literature allowed to delimit these approaches in six areas: political, cultural, territorial, social entrepreneurship and organizational innovation. This study considers the territorial axis as a basis, which considers the SI as Moulaert et al. (2005) as the creation or modification of a product, service or program that changes the status quo of civil society to improve the quality of life of participants as the vision of territorial axis. To reach that goal, it is held in a pragmatic philosophical concept using a mixed methods approach with a corporate strategy concomitant predominantly qualitative. The quantitative inputs were obtained from a questionnaire answered by 63 farmers from a universe of 164 projects Mandalla listed at the Secretary of Agrarian Development in 2012. Qualitative variables were collected through a semi-structured questionnaire applied 8 farmers participating in the project, the first service agent and coordinator. The Project Mandalla is characterized as SI to generate better quality of life for the community and present the characteristics of novelty, intangibility, uncertainty and ubiquity. The project showed the phases of questioning, expression of interest, design and coordination involving the successful diffusion of social innovation. The determinants of success of Butkneivcie (2010) of cultural acceptance, economic, technological feasibility, knowledge sharing, individual entrepreneurship, capital, bottom-up initiatives were also present in this innovation allowing the proposition of a model analysis. In short, the Mandala Project is a successful SI and the adopters perceive social change after deployment when considering gains in food security, sustainability, and feeling pleasure in work, besides improving their economic situation.